Angels and demons are still among us: further validation of the belief in pure evil and belief in pure good scales - Webster, Russell J. (Kansas State University, 2012)
Three studies were conducted to further validate the belief in pure evil (BPE) and belief in pure good (BPG) scales (Webster & Saucier, 2012). Study 1 assessed the relationships between BPE, BPG, and sociopolitical ideology, while Study 2 assessed the relationships between BPE, BPG, and various forms of religiosity. Study 1 and Study 2 also tested whether BPE and BPG predicted aggression and helping via support for relevant foreign (Study 1) or domestic (Study 2) policy issues above and beyond sociopolitical attitudes and religiosity, respectively. Study 3 tested whether BPE and BPG predicted evaluations of a prototypically (vs. non-prototypically) evil perpetrator and a prototypically (vs. non-prototypically) good apprehender. Together, these three studies showed that BPE consistently related to greater aggression and less helping, while greater BPG consistently related to less aggression and more helping, while demonstrating convergence but not redundancy with variables known to justify/suppress aggression or helping. In sum, these studies further demonstrate the reliability and validity of the BPE and BPG scales as well as provide solid groundwork for future correlational and experimental research on these constructs.
Keywords: Pure evil; Pure good; Attributions; Aggression; Antisociality; Prosociality; Psychology (0621); Psychology, Behavioral (0384); Social Psychology (0451)